The impact of China on the steel industry value chain in South Africa and the role of government's industrial policies - Thulare, Jacob (My University, 2016)
China has recently been seen as the most dominant and the fastest growing economy in the world. There has been a lot of pressure on South African Steel products to compete with Chinese steel products in South Africa and the rest of the world market’, and so far South Africa is trailing behind China. Given this poor performance, concern is raised whether government policies may have a role to play in the prospects of the steel industry value chain in South Africa. It is of interest to define what role government policies have on the steel industry value chain and their ability to compete with China, and to suggest how these policies could be refined so that they can boost the South African Steel Industry and its value chain. This study aims at investigating the Impact of China on the Steel industry value chain in South Africa and the role of Government policy. In this study, data is collated through literature from previous studies, electronic surveys and interviews with relevant personnel within the steel industry value chain, and then analysed through SPSS and content analysis. The study considers the challenges faced by the steel industry value chain in South Africa, which also prevents this industry to compete better with China, both in the domestic market and abroad including the relative ease of importing and exporting steel and steel related products between South Africa and China, the impact of increased imports on the South African Steel Industry value chain and whether government policies play any role in averting the likely negative impact. The conclusion of this study is that South African policies do not effectively support the steel industry and its value chain, and the main problem is in implementation rather than the policies themselves. Factors deterring the successful implementation of South African policies are also highlighted in the report.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters in Engineering (MECN 7018). Date: 1 7 June 2015